اضطراب شحوم الدم عند الأطفال البدينين ومفرطي الوزن - Shreitah, Ahmad; Marrousheiah, Faisal; Barjas, Marwa (Latakia University Journal -Medical Sciences Series, 2019)
اضطراب شحوم الدم عند الأطفال البدينين ومفرطي الوزن أحمد شريتح فيصل مروشية مروه برجس أهمية وهدف البحث: يعتبر اضطراب شحوم الدم عامل خطر لتطور الأمراض القلبية الوعائية، والتي تصنف السبب الأول للوفيات حول العالم. تم إجراء هذه الدراسة لتحري حدوث وأنماط اضطراب شحوم الدم عند الأطفال البدينين ومفرطي الوزن. طرق البحث: تم إجراء دراسة مقطعية عرضانية استطلاعية على 126 طفل بدين ومفرط الوزن(BMI≥85th) ، بعمر 6-12 سنة من المراجعين لعيادة أمراض الغدد الصم في مستشفى تشرين الجامعي في اللاذقية في عامي 2017-2018. تم إجراء معايرة صيامية لـ TC, TG, LDL, HDL . النتائج: بلغت نسبة اضطراب شحوم الدم في الجمهرة المدروسة 57,93 %. ازدادت نسبة الإصابة مع زيادة مشعر كتلة الجسم لتصل إلى 76,7% عند شديدي البدانة (P-Value= 0.003). بلغت نسبة ارتفاع الشحوم الثلاثية 42.06%، تلاها انخفاض HDL بنسبة 29.39%. ارتبطت الشحوم الثلاثية مع مشعر كتلة الجسم بعلاقة ارتباط إيجابي (R=0.2)، بينما كانت العلاقة بين HDL ومشعر كتلة الجسم علاقة ارتباط سلبية (R= -0.21). الاستنتاجات: يعتبر الطفل البدين معرض لخطر الإصابة باضطراب شحوم الدم، ويزداد هذا الخطر مع زيادة شدة البدانة، كذلك تزداد شدة الاضطراب في الشحوم الثلاثية و HDL مع زيادة تصنيف البدانة، مما يؤكد على أهمية الاستقصاء عن هذه الحالة المرضية عند كل طفل بدين. Objective: Dyslipidemia is recognized as a prominent risk factor for cardiovascular disease, which consider the leading cause of death globally. The aim of this study is to evaluate the incidence rate and pattern of dyslipidemia in overweight and obese children. Methods: A cross-sectional pilot study on 126 children (BMI ≥ 85th percentile) aged 6-12 years undertaken at the outpatient pediatric endocrine clinic of the Tishreen University Hospital in Lattakia between" 2017-2018. Fasting lipid profile (TC, TG, LDL, and HDL) was obtained. Results: The total incidence rate of dyslipidemia was 57.93%. The incidence rate of dyslipidemia increased with increase BMI and reached 76,7% in the severe obese (P-Value= 0.003). High triglycerides was the most common component of dyslipidemia (42.06%), then low HDL (29.39%). There was a positive correlation between BMI and TG (R=0.2), and an inverse correlation between BMI and HDL (R=-0.21). Conclusions: Obese children are at risk of dyslipidemia, and this risk increase in severe obesity. There is a significant correlation between disturbance of TG, HDL and the severity of obesity .This findings emphasize the need to pay further attention to the screen dyslipidemia in these populations.